Using time stream Petri nets for workflow modelling analysis and enactment. (January 2013) - Cicirelli, Franco; Furfaro, Angelo; Nigro, Libero
Timing requirements are important aspects in workflow modelling, analysis and enactment. In the last few years, though, many workflow languages and tools have been proposed but only few of them address timing issues during enactment. This paper shows that time stream Petri nets (TSPNs), originally designed for multimedia/hypermedia modelling and analysis, are a well-suited formalism also for supporting the whole lifecycle of workflow processes with timing constraints. A novel approach to modelling, analysis and distributed enactment of workflow processes specified by TSPNs is proposed. Functional and temporal properties of a TSPN model can be checked using exhaustive verification or a DEVS-based simulation tool. Enactment rests on PN-Engine, a decentralized enactment engine based on the service-oriented computing paradigm, which enables execution of workflow processes where the coordinated activities may involve cross-boundary organizations. The approach is illustrated by means of a modelling example concerned with a wine-production process.